2021
DOI: 10.1111/ijd.15897
|View full text |Cite
|
Sign up to set email alerts
|

Thrombosis of the palmar digital vein after Oxford‐AstraZeneca COVID‐19 vaccination

Abstract: 10 days after the onset of systemic symptoms, however, 14.7% of patients had skin lesions as their first symptom.Interestingly, our patient's cutaneous findings were the only manifestation of this viral illness. He had no history of allergy or any similar hands or feet manifestations in the past, and his RT-PCR became negative concomitantly with the resolution of the dermatological manifestations. All in all, these findings are in favor of a viral-induced skin eruption associated with COVID-19. While recogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…More recent possible triggers for palmar vein thrombosis include COVID-19 infection [ 7 ] and the COVID-19 vaccine. The latter was reported 8 days after vaccination with a first dose of the Oxford-AstraZeneca COVID-19 vaccine [ 10 ] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent possible triggers for palmar vein thrombosis include COVID-19 infection [ 7 ] and the COVID-19 vaccine. The latter was reported 8 days after vaccination with a first dose of the Oxford-AstraZeneca COVID-19 vaccine [ 10 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Conservative treatment included massaging the nodule and hot compresses [ 15 ] . In the case of thrombosis secondary to hypercoagulable states, treatment also included compression bandaging [ 2 ] , aspirin [ 2 ] and rivaroxaban [ 10 ] . Surgical excision is almost always curative and considered when the lesion is causing discomfort to the patient or if the clinical diagnosis is uncertain [ 15 ] .…”
Section: Discussionmentioning
confidence: 99%
“…In cases where the same sample was used for more than one study, all studies were reviewed to determine the extent to which there may be duplication in the reported outcomes between studies. The full text of selected studies was reviewed, and data on demographics, article type, number of reported cases with cutaneous involvement, vaccine, and rash type (morphology) were extracted from articles texts, tables, figures, and summarized through a descriptive table (Table 1)…”
Section: Methodsmentioning
confidence: 99%
“…), 1 Covishield (Nagrani et al106 ), 1 Moderna (Pesqu e et al154 ), 1 Pfizer (Ricardo et al168 ), 1 Pfizer (Song et al200 ) 69. ), 2 Pfizer (Gruenstein et al109 ), 1 Astrazeneca (Chen et al132 ), 1 Pfizer (Aoki et al144 ) 92. ), 1 Not specified (Dash et al115 ), 1 Pfizer (Holmes et al124 ), 1 Pfizer (Tihy et al130 ) 30.…”
mentioning
confidence: 99%